1999
DOI: 10.5144/0256-4947.1999.447
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of IgE Antibodies Specific to Inhalant and Food Allergens in Adult Asthmatic Patients in Riyadh, Saudi Arabia

Abstract: The number of studies examining the influence of allergies on the natural history of asthma in adults is relatively few. Most of these patients are thought to have intrinsic asthma and, therefore, allergy evaluation is not performed as a routine investigation. However, recent studies have provided some evidence that allergy may play a role in adults with asthma. It has been shown that the frequency of immediate skin test reactivity in these patients was high, ranging from 58% to 80%.1,2 A recent study by Lin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
4
3
0
Order By: Relevance
“…Results of children were almost in accordance with the reported percentage in Spain (4.7 per cent) (Venter et al, 2006) and in the USA (4.8 per cent) (Salo et al, 2014). However, it was less than the rate reported in other countries such Turkey (10.1 per cent) (Orhan et al, 2009), Saudi Arabia (13 per cent) (GadElRab, 1999) and France (11.9 per cent) (Rance et al, 2005). Moreover, in atopic populations, data showed higher values; Egypt (10.2 per cent) (World Notes: N T : number total of person reporting milk allergy; N: number of person reporting allergy to each milk specie within the population reporting milk allergy…”
Section: Discussionsupporting
confidence: 84%
“…Results of children were almost in accordance with the reported percentage in Spain (4.7 per cent) (Venter et al, 2006) and in the USA (4.8 per cent) (Salo et al, 2014). However, it was less than the rate reported in other countries such Turkey (10.1 per cent) (Orhan et al, 2009), Saudi Arabia (13 per cent) (GadElRab, 1999) and France (11.9 per cent) (Rance et al, 2005). Moreover, in atopic populations, data showed higher values; Egypt (10.2 per cent) (World Notes: N T : number total of person reporting milk allergy; N: number of person reporting allergy to each milk specie within the population reporting milk allergy…”
Section: Discussionsupporting
confidence: 84%
“…The food allergens take place with less frequency. 10,11) Also in our study, Inhalant allergens (AlaTOP) were also found to be more frequently positive than food allergens (FP5) among allergic patients. We investigated the allergens in sera by using the AlaTOP and FP5.…”
Section: Discussionsupporting
confidence: 65%
“…Dermatophagoides pteronyssinus, Dermatophagoides farinae, Felis domesticus, pollen allergens and Timothy grass are seen most frequently and they are widespread in the world. 10,12) However, distribution of allergens changes according to regions. Dermatophagoides pteronyssinus (43%), Dermatophagoides farinae (32%) and Timothy grass (46%) could be important allergens among patients also in our study (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…GadElRab [28] in a study of 217 patients suffering from asthma, rhinitis and urticaria in Riyadh, Saudi Arabia found 17.5% to have specific IgE antibodies to various foods. The most common sensitivities were to peanut (23%), egg (15%) and cow’s milk (13%).…”
Section: Introductionmentioning
confidence: 99%